Effects of stricter management guidelines on return-to-competition time frames following concussion in professional Australian Rules football: an exploratory analysis - Pearce, A. J.; King, D. A.; White, A. J.; Suter, C. M. (Sports Medicine, 2021)
Background: Management of concussion remains a serious issue for professional sports, particularly with the growing knowledge on the consequences of repetitive concussion. One primary concern is the subjective assessment of recovery that dictates the time until a concussed athlete is returned to competition. In response to this concern, the Australian Football League (AFL) changed its policy in 2020 such that medical clearance for return-to-competition was extended from one day, to a minimum of five days, prior to the next scheduled match. Objective: We sought to explore the impact of the AFL policy change by asking whether time to return-to-competition after concussion was increased in the 2020 season relative to previous years. Methods: Retrospective data on injury and return-to-competition were sourced from publicly available tables published by the AFL. Our primary exploration compared the number of matches missed and the number of days missed in concussed players across 2017 to 2020 inclusive, with secondary exploration analysing the proportion of players returning to play 12 days or longer. Results: Analysis of data from 166 concussed players revealed no increase in the number of matches missed in 2020 relative to previous years as would have been expected from an extended recovery protocol. Comparing 2020 relative to 2017-19 we found that there was an overall moderate reduction in median time to return-to-competition (RTC) in 2020 (10 vs 13 days, respectively d=-0.345)) and a significant reduction in players taking more than 12 days to RTC (p=0.046). Conclusion: This exploratory study demonstrates that clubs may not have followed policy change around concussion management designed to increase time to RTC. Ongoing auditing is required to ensure player clearance meets policy goals, highlighting the need for objective measures for RTC after concussio.